THE EFFECTIVENESS OF BLADDER TRAINING ON ACCELERATING URINE OUTPUT IN NORMAL POSTPARTUM AT ACEH SINGKIL REGIONAL GENERAL HOSPITAL - Cut Mainy Handiana; Eva Zulisa; Nurul Husna; Yuliza Andari (Soscience: Jurnal Ilmu Sosial Science, 2026)
Urinary retention is a common postpartum problem characterized by the inability of mothers to urinate spontaneously after childbirth. If not managed properly, postpartum urinary retention may cause discomfort, urinary tract infections, and impaired uterine contraction. Bladder training is a non-pharmacological intervention that can be applied to prevent and accelerate urinary elimination after delivery. In 2024, cases of postpartum urinary retention were still reported at Aceh Singkil Regional General Hospital, indicating the need for early intervention. This study aimed to determine the effectiveness of bladder training in accelerating the first urination time among normal postpartum mothers at Aceh Singkil Regional General Hospital. This study employed a quasi-experimental design with a non-equivalent control group approach. A total of 20 normal postpartum mothers were selected as samples and divided into an intervention group that received bladder training and a control group that received standard care. Data were collected through direct observation of the time to first urination, measured in hours, and analyzed using the Independent T-Test. The results showed that the intervention group had a faster average time to first urination (2.98 hours) compared to the control group (5.5 hours). Statistical analysis demonstrated a significant difference between the two groups (p = 0.00034; p < 0.05). These findings indicate that bladder training is effective in accelerating first urinary elimination in normal postpartum mothers and can be recommended as an early non-pharmacological intervention in postpartum care.